Causal Relationship Model Affecting the Efficiency of Container Freight Transport in Thailand - อาสอภิสิทธิ์, บุญชัย; สหายา, นนท์ (The Journal of Development Administration Research, 2025)
This research aims to 1) study the causal factors of business competition, value chain, and human resource management that affect the efficiency of container shipping in Thailand and 2) propose guidelines for improving the efficiency of container shipping in Thailand. The quantitative research sampled 340 container shipping operators in Thailand. The sample size was set at 20 times the observed variable. The stratified random sampling was used to collect data. The data was analyzed using structural equation modeling. For the qualitative research, in-depth interviews were conducted with 3 officers from the Thai Freight Forwarding and Logistics Association and 13 representatives from container shipping operators in Thailand. The data was analyzed using content analysis. The results of the research found that 1) business competition had the highest influence on the efficiency of container shipping in Thailand, followed by value chain and human resource management, respectively. 2) Guidelines for improving the efficiency of container shipping in Thailand were a newly developed model called the “BVHT Model” that focuses on quality, workload, time, cost, and method.